Antimicrobial Properties of Vitamin B2. Issue 5 (3rd May 2016) - Ahgilan, Aarthi; Sabaratnam, Vikineswary; Periasamy, Vengadesh
Abstract : Riboflavin or B2, isolated from a wide variety of animals and plant products is an important vitamin commonly found in the diets of various cultures. This vitamin has been generally known to impart antimicrobial properties when exposed to ultra-violet A irradiation. In the current work, we investigated the possibility of preventing or reducing pathogenic infections using both ultra-violet A assisted and stand-alone riboflavin solutions on selected strains of bacteria. The antimicrobial properties of riboflavin were determined by the effective inhibition of the growth of pathogens through the disc diffusion method. Zones of inhibition studies indicated that riboflavin on its own was found to be quite effective and was able to inhibit the pathogens when diffused at a concentration of 50.0 µL. Stand-alone riboflavin solution successfully inhibited Staphylococcus aureus, Enterococcus faecalis, Salmonella typhi, and Pseudomonas aeruginosa with an inhibition range of (18.7 ± 0.6) mm; (17.7 ± 0.6) mm; (17.3 ± 0.6) mm, and (15.7 ± 0.6) mm, respectively. Intermediate zones of inhibition were observed for Escherichia coli and Candida albicans with a range of (11.7 ± 0.6) mm and (11.7 ± 0.6) mm, respectively. Klebsiella pneumoniae was the only resistant pathogen at (7.7 ± 0.6) mm for the riboflavin concentration used in this work. These results may indicate the exciting prospects of the applications of riboflavin as a complementary approach toward inactivation of pathogenic infections.